APPLYING MARKETING CONCEPTS IN CHEESEMAKING BUSINESS ENTITIES IN THE REPUBLIC OF SERBIA - Radojević, Vuk; Užar, Dubravka Petar; Mugoša, Izabela (Economics of Agriculture, 2020)
Main objective of the research is to identify role and position of marketing in business practice in micro, small and medium-sized enterprises (MSME) in the Republic of Serbia. Since cheese is a value-added product, cheesemaking takes a significant position in countrys food chain and represents a significant revenue generator for every participant in the production cycle. Lack or insufficient usage of marketing decreases the possibilities of efficient and effective use of resources and minimizes cheesemakers competitive advantage. The research has been conducted in the form of a questionnaire by using a random sample of 39 business entities in the territory of the Republic of Serbia. Research results indicate that marketing is at a peripheral position in the business practice of the analysed business entities. Main precondition for marketing concept implementation is introduction of marketing function and formalized process of marketing planning integrated into corporate planning system and supported by each level of management structure.